Från trafikövervakning till trafikledning – En studie om olyckor kan reduceras i Göteborgs VTS-område med trafikledningssystem - Boholm, Daniel; Näslund, Elinor (My University, 2017)
The Port of Gothenburg is the largest port in Scandinavia. Every year a large amount of cargo and passenger vessels pass in and out through the harbor inlet of Gothenburg. In the archipelago the merchant shipping has to get along well with other types of vessels such as pleasure crafts and working vessels, which also form a part of the maritime traffic in the VTS-area. The study highlights the general provisions of the area as pilotage and pilotage exemption, the Collision Regulations on narrow fairway and traffic separation schemes as they are relevant to the area of the current situation and possible changes, including different technical aspects that contribute to increased safety are described. Sometimes the high traffic intensity causes trouble for all the vessels, and sometimes accidents occur. Yet more often to occur, are incidents of varying significance, with a frequency as high as up to several times per week. In the report, some of the more serious incidents that have occurred over the years are presented. Critical areas that are in direct need for actions will also be identified, where the focus mainly being on the area around the Trubaduren lighthouse and the anchoring areas available in the VTS area. The study aims to answer questions regarding whether the introduction of a traffic management system is a possible solution to reduce the number of incidents. The study highlights the different types of traffic management systems that can be alternative solutions to make the traffic more effective and contribute to a lower risk of close navigation situations and the advantages and disadvantages of various options. The question is answered through semi-structured interviews with people who daily are directly involved in the harbor activities. The interviewees were five VTSO, four pilots and one person from a shipping company that operates Gothenburg gives, through their experiences, answers that later can be discussed. Also an observation was made in connection with interviews VTS Gothenburg to get an understanding of how traffic monitoring functions in the current situation. The study shows that a combined form of traffic management systems can reduce the risk of future accidents and incidents in Gothenburg VTS area.
Keywords: Transport; Annan teknik; Transport; Other Engineering and Technologies